Decent work conditions and good living for the full development of the capacities of Colombian workers - Vargas Prieto, Amanda; Cruz Suárez, Duvier Felipe; León Acuña, Laura Marcela (Cooperativismo & Desarrollo, 2021)
The article raises the possibility of implementing the concept of good living in decent working conditions for the full development of the capabilities of workers in Colombia. Through a phenomenological methodology, three main results were found. It shows that it is not possible to implement good living since there are no decent work conditions for the full development of the capabilities of Colombian workers. The description of the current working conditions of the worker shows that it is not possible to implement good living for the development of skills due to the fact that more time is dedicated to the production of income and other principles that make up the good life are ignored, such as affiliation and the harmony with others. However, there is evidence of the need to configure profound changes in the working conditions of Colombian society that include the real implementation of decent work and decent work in the framework of good living for the full development of capabilities.